Congenital diaphragmatic hernia as a prominent feature of a SPECC1L‐related syndrome. Issue 12 (21st September 2020) - Wild, K. Taylor; Gordon, Tia; Bhoj, Elizabeth J.; Du, Haowei; Jhangiani, Shalini N.; Posey, Jennifer E.; Lupski, James R.; Scott, Daryl A.; Zackai, Elaine H.
Abstract: Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in 30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X‐linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L‐ related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L‐ related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.